There Is No Elevation of Immunoglobulin E Levels in Albanian Patients with Autoimmune Thyroid Diseases. (13th May 2014) - Latifi-Pupovci, Hatixhe; Gacaferri-Lumezi, Besa; Lokaj-Berisha, Violeta
Abstract : Background . Studies in several ethnic groups reported high incidence of elevated levels of immunoglobulin E (IgE) in patients with autoimmune thyroid diseases (ATD), especially in patients with Graves' disease. Objective . To study association between serum levels of IgE and thyroid stimulating hormone receptor antibodies (TRAb) in Albanian patients with ATD. Material and Methods . Study was performed in 40 patients with Graves' disease, 15 patients with Hashimoto's thyroiditis, and 14 subjects in the control group. The IgE levels were measured by immunoradiometric assay, whereas the TRAb levels were measured by radioreceptor assay. Results . In all groups of subjects the IgE levels were within reference values (<200 kIU/L). Significant difference in mean concentration of IgE was found between two groups of Graves' disease patients, and those with normal and elevated TRAb levels (22.57 versus 45.03, P < 0.05 ). Positive correlation was found between TRAb and IgE only in Graves' disease patients (r = 0.43, P = 0.006 ). Conclusion . In Albanian patients with ATD there is no elevation of IgE levels. This could be the result of low prevalence of allergic diseases in Albanian population determined by genetic and environmental factors.